Forest tree breeding under the global environmental change: Challenges and opportunities - Chenglin Li; Baochen Li; Wenxuan Zhao; Jiebei Jiang; Jieshi Tang (Trees, Forests and People)
Forests are essential for global ecological, economic, and social stability; however, they are increasingly threatened by global environmental changes. Traditional breeding methods like marker-assisted and genomic selections have long been used in forest tree improvement to address these challenges. However, the long generation times and complex genetics of forest trees limit their effectiveness. Molecular genetic breeding of forest trees has emerged as a transformative strategy to enhance resilience and adaptability. Gene-editing technology advances, such as CRISPR-Cas9, have enabled precise genetic modifications to improve traits such as drought tolerance, pest resistance, and growth rates. Additionally, innovative techniques, such as gene and cell engineering, are being explored to increase genetic diversity and enhance tree performance under changing environmental conditions. However, challenges, such as regulatory concerns, scalability, and trait stability, remain. We examined the current state of the molecular genetic breeding of forest trees, highlighting their unique roles in addressing specific challenges. We evaluated the advantages and limitations of traditional and innovative approaches, emphasizing the need for their integration to develop tree varieties capable of thriving under global environmental change. These efforts are vital for sustainable forest management, biodiversity conservation, and carbon sequestration enhancement, ultimately contributing to forest ecosystems' long-term health and stability.